Islamic Education Methods (Comparative Study of the Thoughts of Abdurrahman An-Nahlawy and Khalid bin Hamid Al-Hazimi) - Sari, Hannisa Wandan; Wahyudi, Hakmi (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research is motivated by the many phenomena of moral degradation carried out by students. Therefore, efforts need to be made to find alternative solutions to provide better character education to students. One of the efforts is to reopen and examine the differences in thoughts of previous Islamic education figures regarding educational methods.The aims of this research are 1) To find out educational methods according to the ideas of Abdurrahman Nahlawy and Khalid bin Hamid Al-Hazimi 2) To find out the comparison of Abdurrahman Nahlawy and Khalid bin Hamid Al-Hazimi's ideas about educational methods. This research is qualitative research with the type of library research. Meanwhile, the data collection technique used is the documentary method and the data analysis technique uses content analysis and comparison methods. Based on the research results, it can be seen that Abdrurahman Nahlawy has seven educational methods, while Al-Hazimi has five methods. According to the author's analysis, the main aim of all methods in the second book is to touch students' emotions.The similarities in methods between the two images above are examples, stories, tips and targhib wa tarhib methods. Meanwhile, the differences in methods lie in the methods of dialogue, story-telling, training and practice, and punishment method.